2011
DOI: 10.1007/s10457-011-9423-2
|View full text |Cite
|
Sign up to set email alerts
|

Landscape vulnerability to wildfires at the forest-agriculture interface: half-century patterns in Spain assessed through the SISPARES monitoring framework

Abstract: Large-scale socioeconomic changes in recent decades have driven shifts in the structure of Spanish rural landscapes, particularly in those located at the forest-agriculture interface (FAI), as well as in their wildfire regime. Using data from more than 200 16 km 2 landscape plots in Spain surveyed between 1956 and 2008 through the SISPARES monitoring framework, we assessed the FAI vulnerability to wildfires and identified the main landscape structural factors related to an increased number of wildfire events. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
47
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 46 publications
3
47
0
2
Order By: Relevance
“…This has a positive influence in many studies (Cardille et al, 2001;Maingi and Henry, 2007;RomeroCalcerrada, 2008;Catry et al, 2009;Sebastian-Lopez et al, 2008;Martínez et al, 2009;Marques et al, 2011;Nunes, 2012) or a negative relationship for some areas in other studies (Narayanaraj and Wimberly, 2012; Sá et al, 2011). Additionally, the previously mentioned variables were also related with the CORINE land use class "agriculture but with significant areas of natural vegetation" (CL 21 PM), showing that fire occurrence was more likely in municipalities where agricultural and forest areas are intermixed, similar to what has been reported by Ortega et al (2012). Recently, when trying to explain the extreme 2007 fires in the Greek Peloponnese, observed that the CORINE land cover category "agricultural land, highly interspersed with significant areas of natural vegetation" was the most affected by fire, reflecting the encroachment of natural vegetation in abandoned fields and also recent patterns of evolution in the wildland-rural interface where agricultural land is increasingly intermixed with natural vegetation.…”
Section: Driving Factors Of Long-term Fire Presencesupporting
confidence: 74%
See 2 more Smart Citations
“…This has a positive influence in many studies (Cardille et al, 2001;Maingi and Henry, 2007;RomeroCalcerrada, 2008;Catry et al, 2009;Sebastian-Lopez et al, 2008;Martínez et al, 2009;Marques et al, 2011;Nunes, 2012) or a negative relationship for some areas in other studies (Narayanaraj and Wimberly, 2012; Sá et al, 2011). Additionally, the previously mentioned variables were also related with the CORINE land use class "agriculture but with significant areas of natural vegetation" (CL 21 PM), showing that fire occurrence was more likely in municipalities where agricultural and forest areas are intermixed, similar to what has been reported by Ortega et al (2012). Recently, when trying to explain the extreme 2007 fires in the Greek Peloponnese, observed that the CORINE land cover category "agricultural land, highly interspersed with significant areas of natural vegetation" was the most affected by fire, reflecting the encroachment of natural vegetation in abandoned fields and also recent patterns of evolution in the wildland-rural interface where agricultural land is increasingly intermixed with natural vegetation.…”
Section: Driving Factors Of Long-term Fire Presencesupporting
confidence: 74%
“…6. Another important variable was forest-cultivated land interface (ICFSUP P), which is related to agricultural activities where fire is frequently used in arable and crop lands, , Ortega et al, 2012Gonzalez-Olabarría et al, 2012), which found that the landscapes most vulnerable to fire were those with fine-grained forest-agriculture mixtures or mosaics, where the humancaused fires were more intense than homogeneous and nonfragmented landscapes. Variables DIS 50 91 (population decrease between 1950 and 1991) and DIS SAU (decrease in agricultural area between 1989 and 1999) were positively correlated with the occurrence of at least one fire event.…”
Section: Driving Factors Of Long-term Fire Presencementioning
confidence: 99%
See 1 more Smart Citation
“…Among the studies that have dealt with fire occurrence in the literature, many have included geographic or spatial variables (i.e. Padilla and Vega-García, 2011) but only Henry and Yool (2004), Martínez et al (2009) and Ortega et al (2012) have included independent variables measuring landscape pattern. Henry and Yool (2004) calculated landscape metrics (area, shape and diversity indices) in remote sensing images (Landsat TM and SIR-C data) to relate landscape pattern with historical fire occurrence in National Saguaro Park (Arizona).…”
mentioning
confidence: 99%
“…Martí-nez et al (2009) considered area, density and fragmentation indices (landscape and cropland fragmentation) with socio-economical and geographical variables to predict human-caused fire occurrence at the municipal scale in Spain. A recent study by Ortega et al (2012) did analyze landscape structural factors (11 metrics) related to increased wildfire incidence in forest-agriculture interfaces within the SISPARES monitoring network (observation size 16 km 2 ), finding that certain landscape configurations were more vulnerable (fireprone) than others.…”
mentioning
confidence: 99%